Caractérisation des peuplements de macroinvertébrés benthiques à l’aide de la carte auto-organisatrice (SOM) - ADANDEDJEAN, DELPHINE; LALEYE, PHILIPPE A. (My University, 2013)
Macrobenthic organisms are much used nowadays as bio-indicators for their ability to reflect different disturbances of aquatic ecosystems. However, they have never been used to assess the ecological status of the lagoons of Benin. The current study aims at revealing the ecological state of the lagoon of Porto-Novo through the study of changes in the settlement of benthic organisms collected in this lagoon. The sampling was carried out from July 2007 to June 2009 on a frequency of four seasons of collection per year. The self-organizing map (SOM) of Kohonen has been used for various patterns of distribution of collected organisms. A discriminant analysis (AFD) has allowed the identification of the parameters that govern the patterns observed in this environment. Four groups of macrobenthic communities emerged that were well predicted (75%). The distribution of benthic macro invertebrates of this lagoon is therefore zonal, seasonal and discriminated by variables of mineralization and sediment grain size. The difference in taxonomic richness corresponds to environmental conditions of stations appearing more or less stable and highlighting a gradient of the stress on organisms. Places with unstable conditions are affected by human activities due to their proximity to homes that are enriched in organic matter. These places are full of polluted-tolerant species such as the Gastropods Potamididae, Cirratulidae Polychaetes, Diptera Chironomidae and Oligochaeta. The macrobenthic fauna, which is well differentiated in the groups, is then subjected to human disturbance.
Keywords: Benthic macrofauna; Lagoon; SOM Distribution; Stress Benin.